Exploring The Influence Of Safety Culture And Employee Safety Behavior On Job Satisfaction In The Vidarbha Region's Iron And Steel Sector: An Empirical Investigation (Journal of Namibian Studies : History Politics Culture, 2023)
Risk management is a strategic challenge for manufacturing companies due to the high stakes involved in ensuring worker and customer safety. However, it is unclear whether or not the use of many instruments to evaluate and track safety performance has any effect on the overall safety atmosphere and culture in the workplace. Employee involvement is investigated as a potential mediating factor between safety culture and environment and safety performance in India's industrial industry. Purposive sampling was used to pick 368 participants from among employees of five large-scale industrial manufacturing companies for this quantitative study. SPSS 23 was utilised for a number of different methods to be combined into one, such as structural equation modelling, growth trajectories, and a correlation matrix. Using these approaches, a correlation was forged between safety-related factors like culture and environment and concrete metrics like performance. The primary takeaway from the research is that safety atmosphere is important, but that safety culture has an even greater bearing on safety performance. Both the relationship between safety environment and safety performance and the relationship between safety culture and safety performance were significantly mediated by employee involvement. These findings suggest that in order to improve safety performance and overall safety, policymakers and practitioners in large-scale manufacturing businesses in India should give priority to strengthening the company's safety culture and environment.